An evaluation of the pharmacokinetics and pharmacodynamics of ivabradine for the treatment of heart failure. (February 2014) - Rosa, Gian Marco; Ferrero, Simone; Ghione, Paola; Valbusa, Alberto; Brunelli, Claudio
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Ivabradine&logicalOpe1=OR&field2=articletitle&text2=Ivabradine&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Ivabradine is a new heart-rate-lowering drug; the aim of this review was to analyze its role in heart failure (HF). Areas covered: This systematic review on the role of ivabradine in HF is based on material searched and obtained through Pubmed and Medline up to September 2013. Expert opinion: Heart rate (HR) is a risk factor in patients with HF, and its reduction is considered an important goal of therapy. The BEAUTIFUL trial demonstrated the benefits of ivabradine on prognosis (only on ischemic endpoints) in patients with coronary artery disease (CAD) and left ventricular systolic dysfunction (LVSD) and HR ≥ 60 bpm. In the SHIFT trial, which enrolled patients with LVSD, HF and HR ≥ 70 bpm, ivabradine administration (on top of guideline-based therapy, including β-blockers [BB]) was associated with a reduction of cardiovascular death and hospitalizations for HF, but BB were underutilized. Further studies are needed to test the efficacy of ivabradine in CAD patients with high HR and to shed light on the comparison between ivabradine and a more aggressive therapy with higher doses of BB in HF patients.